Desenvolvimento e aplicação de eletrodos compósitos à base de borracha de silicone e grafite - Oliveira, Aline Carlos de (2004)
Composite electrodes were prepared using graphite powder and silicone rubber in different compositions. The use of such hydrophobic materials interned to diminish the swallowing observed in other cases when the electrodes are used in aqueous solutions for a long time. The composites were characterized for the response reproducibility, ohmic resistance, thermal behavior and effective area. The voltammetric response in relation to analysts with knows voltammetric behavior was also evaluated, always in comparison with the glassy carbon. Licrean responses were observed for [Fe(CN)6]3- at 50 and 100 mVs-1 scan rates. The electrode 70% (graphite, w/w) was used in the quantitative determination of hydroquinone (HQ) in a DPV procedure in which a detection limit of 5.08x10-8 molL-1 was observed. Hydroquinone was determined in a photographic developer sample with errors lower then 1% in relation to the label value. Dopamine was also determined using a DPV procedure with detection limit of 1.1x10-6molL-1. When pharmaceutical samples containing dopamine were analyzed errors lower then 5% were observed in relation to the label value.